2013
DOI: 10.1007/s11427-013-4554-5
|View full text |Cite
|
Sign up to set email alerts
|

Non-coding RNAs regulate tumor cell plasticity

Abstract: Tumor metastasis is one of the most serious challenges for human cancers as the majority of deaths caused by cancer are associated with metastasis, rather than the primary tumor. Recent studies have demonstrated that tumor cell plasticity plays a critical role in tumor metastasis by giving rise to various cell types which is necessary for tumor to invade adjacent tissues and form distant metastasis. These include differentiation of cancer stem cells (CSCs), or epithelial-mesenchymal transition (EMT) and its re… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
10
0

Year Published

2014
2014
2024
2024

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 13 publications
(10 citation statements)
references
References 50 publications
0
10
0
Order By: Relevance
“…The EMT is an evolutionary-conserved biological process whereby epithelial cells acquire mesenchymal characteristics, and is involved in apoptosis resistance, tumor motility, and invasion. Molecules associated with this process are transcription factors, such as ZEB (ZEB1 and 2), Snail, Slug, and Twist1, which act by repressing E-cadherin and inducing vimentin and fibronectin expression (21). The EMT process is strongly regulated by miRNAs; for example, the miR-106b-25 cluster has been shown to induce the EMT and CSC phenotype in human breast cancer cells, acting downstream of the transcription factor Six1.…”
Section: Cancer Stem Cells and Oncomirnasmentioning
confidence: 99%
“…The EMT is an evolutionary-conserved biological process whereby epithelial cells acquire mesenchymal characteristics, and is involved in apoptosis resistance, tumor motility, and invasion. Molecules associated with this process are transcription factors, such as ZEB (ZEB1 and 2), Snail, Slug, and Twist1, which act by repressing E-cadherin and inducing vimentin and fibronectin expression (21). The EMT process is strongly regulated by miRNAs; for example, the miR-106b-25 cluster has been shown to induce the EMT and CSC phenotype in human breast cancer cells, acting downstream of the transcription factor Six1.…”
Section: Cancer Stem Cells and Oncomirnasmentioning
confidence: 99%
“…EMT is involved in apoptosis resistance, tumor motility and invasion. Molecules associated with this process include transcription factors, such as the zinc-finger E-box-binding homeobox proteins (ZEB1 and 2), Snail, Slug and Twist1, which repress E-cadherin and induce vimentin and fibronectin expression [50]. The EMT process is also strongly regulated by miRNAs.…”
Section: Key Termsmentioning
confidence: 99%
“…Although these classes constantly change and increase (Brown et al 2012;Sana et al 2012), most of the authors group these transcripts by their size into small ncRNAs and long ncRNAs (lncRNAs) (Gutschner and Diederichs 2012;Sana et al 2012;Liu et al 2013). Each of these groups is further subdivided, giving rise to a large number of different types of ncRNAs needing urgent and adequate characterization (Sana et al 2012;Deng and Sui 2013), namely, satellite DNA transcripts.…”
Section: Introductionmentioning
confidence: 99%
“…Lastly, satncRNAs have been associated with cancer (Ehrlich 2005;Ting et al 2011;Zhu et al 2011;Brown et al 2012). In fact, the recent advances in the study of ncRNAs enhance the involvement of these transcripts and their aberrant expression in cancer pathogenicity (Gutschner and Diederichs 2012;Deng and Sui 2013;Feldstein et al 2013;Hauptman and Glavac 2013;Liu et al 2013) since initiation, to progression, and until metastasis (Hauptman and Glavac 2013). Although the knowledge about satncRNAs is scarce, it is now suggested that these transcripts may play a role in the evolution of cancer cells by their function in at least one of the cancer hallmarks-genomic instability (Zhu et al 2011;Brown et al 2012;Walton et al 2014).…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation